Identification of Farmers Knowledge on Rice Straws Technology for Beef Cattle Development in Enrekang Regency - Abdullah, Agustina; Hastang, Hastang; Amrawati, A. A.; Jamila, Jamila (Proceeding INTERNATIONAL SEMINAR IMPROVING TROPICAL ANIMAL PRODUCTION FOR FOOD SECURITY)
The objective of this study was to identify the farmers knowledge in utilize of the rice strawsto have value added through innovative processing technologies for the development of beef cattle. This study was conducted in Sub-district of Maiwa, Enrekang Regency, South Sulawesi.Determination of farmers as respondents was randomly based on the Slovin method. The number ofrespondent was 60 farmers.  Data was collected through survey research using data collectiontechniques such as interviews and questionnaire, focus group discussion and in depth interview withkey informants.  The results of this study showed that, in general (90% of the respondents) thefarmers know the information regarding rice straws technology.  However, it was only 46.9% of therespondents apply this technology for their cattle. As conclusion, it is necessary to improve and tooptimize in applying rice straws technology for development of beef cattle in smallholder farms.Key Words: Knowledge, Farmer, Beef Cattle, Technology, Rice Straws